Occupy this: why some colleges had Occupy Wall Street protests. Issue 2 (2nd September 2017) - Asal, Victor; Testa, Alexander; Young, Joseph
Abstract: During autumn 2011, Occupy Wall Street protests began rapidly emerging at college and university campuses across the United States. Many of these student groups developed an agenda based on localized issues at their particular college. Still, nearly all Occupy student protests also followed the common goal of bringing change to a system plagued with an inequality gap between the "99 and 1 percent", massive financial debt, rising tuition costs, and a poor labour market for students who spend thousands of dollars for their education. While these students are taking aim at large, powerful, "elitist" institutions, data indicate that these protestors belong to institutions similar to those they are opposing. Our data from 191 colleges and universities with an "Occupy" event indicate that protests are more likely to occur at four-year institutions that have a largely white population. Additionally, these protests emerge at institutions with the greatest amount of resources including larger staffs, higher faculty wages, and higher tuition fees.